2012
DOI: 10.2527/jas.2012-5344
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucose and volatile fatty acids on blood ghrelin concentrations in calves before and after weaning1

Abstract: The effects of feeding and intravenous injections of glucose and VFA on blood ghrelin concentrations were investigated in calves before and after weaning. Eight Holstein bull calves were fed whole milk, allowed free access to solid feeds, and weaned at 7 wk. Measurements were carried out at 2, 4, 6, 9, 11, and 13 wk, at which time jugular blood samples were taken from 4 calves through a catheter from 10 min before to 120 min after their morning feed at 10 min intervals (Exp. 1). An additional 4 calves of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Calves with lower intake display higher plasma concentrations of active ghrelin (Bohan et al, 2007), such as MIX calves in wk 8 and 10. The lower starch intake of postweaned MIX calves may have resulted in less rumen fermentation, lower production of VFA, and overall higher plasma ghrelin concentrations (Fukumori et al, 2011(Fukumori et al, , 2012. Starch intake was similar between treatments in the preweaning and weaning periods, which likely explains why no difference in plasma ghrelin concentration was observed during those periods.…”
Section: Postweaning Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…Calves with lower intake display higher plasma concentrations of active ghrelin (Bohan et al, 2007), such as MIX calves in wk 8 and 10. The lower starch intake of postweaned MIX calves may have resulted in less rumen fermentation, lower production of VFA, and overall higher plasma ghrelin concentrations (Fukumori et al, 2011(Fukumori et al, , 2012. Starch intake was similar between treatments in the preweaning and weaning periods, which likely explains why no difference in plasma ghrelin concentration was observed during those periods.…”
Section: Postweaning Periodmentioning
confidence: 99%
“…Plasma GLP-2 concentrations were measured with Eu-labeled human GLP-2 (Peptide Institute Inc., Osaka, Japan), Eu-labeled human GLP-2 (Yanaihara Institute Inc., Shizuoka, Japan), and polystyrene microtiter strips coated with goat-anti-rabbit γ-globulin (Elsabagh et al, 2017). Plasma ghrelin concentrations were measured using Eu-labeled synthetic bovine ghrelin, polyclonal anti-rat ghrelin, and polystyrene microtiter strips (Nalge Nunc Int., Tokyo, Japan) coated with anti-rabbit γ-globulin (Fukumori et al, 2012). The plasma concentration of metabolites were enzymatically assayed on a Beckman Coulter chemistry analyzer (AU480; Beckman Coulter Inc., Brea, CA)…”
Section: Sample Analysesmentioning
confidence: 99%
“…According to current research, it has been suggested that ghrelin may potentially exhibit antioxidant properties via the Nrf2/ARE pathway; however, the precise mechanism behind this phenomenon has yet to be thoroughly investigated ( Cheng et al, 2020 ). Furthermore, ghrelin has been found to stimulate the secretion of growth hormone ( Fukumori et al, 2012 ), and a deficiency in growth hormone has been linked to oxidative stress ( Kokoszko et al, 2008 ). Therefore, it is plausible that ghrelin may also exert antioxidant effects by stimulating the secretion of growth hormone.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the researchers observed that ghrelin demonstrated robust antioxidant capabilities in brain tissue. Given that adult growth hormone deficiency can result in oxidative stress ( Kokoszko et al, 2008 ), and ghrelin possesses the ability to stimulate growth hormone secretion ( Fukumori et al, 2012 ), further investigation is required to determine whether the antioxidant effect of ghrelin is direct or mediated through growth hormone stimulation. A study has demonstrated an association between growth hormone and 30-day mortality following ICH, as well as a deterioration in prognosis after 90 days ( Zweifel et al, 2011 ).…”
Section: Multiple Factors That May Be Used To Treat Ich Through Mgbamentioning
confidence: 99%
“…This fact indicates that increase in plasma insulin concentrations always causes a rise in plasma GH concentrations, and that plasma insulin or glucose levels are not related to the post-prandial reduction in GH levels. The doses of insulin and glucose injection used in the present study have been employed in previous studies [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%